THE LATE FATE OF USING ANTIOXIDANT PREPARATIONS IN THE HOLIATRY OF CHRONIC CATARRHAL GINGIVITIS IN CHILDREN - Годованець, О.І. (World of Medicine and Biology, 2012)
The expediency of using antioxidant preparations in a complex of conventional treatment of chronic catarrhal gingivitis in children upon excessive nitrate entry has been substantiated on the basis of studying the clinical picture and the state of the indices of the prooxidant-antioxidant system in children’s oral fluid in the dynamics of case monitoring. A positive effect of “Proteflazidum” and “Immunoflazidum” preparations on the course of the disease has been established and that is corroborated by an accelerated involution of its clinical manifestations and an enhanced activity of the system of the antioxidant protection of the oral cavity.
Keywords: children; gingivitis; prooxidant-antioxidant system; “Proteflazid”; “Immunoflazid”